Improvement of Sorption Parameters of Nickel Ions on Bentonite in the Result of its Irradiation by Microwaves - Sysa, L.; Shevchuk, L.; Kontsur, A. (Physics and Chemistry of Solid State, 2017)
The adsorption isotherms of nickel ions from aqueous solutions on bentonite, a natural argillaceous material, previously prepared using ultrahigh-frequency electromagnetic waves ("microwaves") were researched in the article. The phase composition of the sorbent was studied by applying the X-ray powder method. Bentonite sample being pre-wetted and irradiated by microwaves shows 2.7 times better sorption properties than the untreated (native) sample, which was shown on the example of the adsorption process of nickel ions from model solutions in static conditions. The sorption parameters prepared by using the "microwaved" and the native samples of bentonite were calculated according to the Langmuir adsorption equations. The barrier density of nickel in the irradiated sorbent is 16.4 mg/g (0.28 mmol/g), whereas for native bentonite the value of the analogous parameter is 6.0 mg/g (0.10 mmol/g). The reason for such an increase in sorption properties may be the change in the crystalline structure and distribution of micropores on the surface of the sorbent under the action of "microwaves" in the aqueous medium. The determinants in the pre-preparation of sorbent by "microwaves" are the ultimate power and time of irradiation.